Dyslogic syndrome why millions of kids are "hyper," attention-disordered, learning disabled, depressed, aggressive, defiant, or violent - and what we can do about it - Rimland, Bernard, 1928-2006 (Jessica Kingsley Publishers, 2008)
Dyslogical children are commonly labelled as having one or more of a mix of conditions that includes bipolar disorder, attention deficit/hyperactivity disorder, and oppositional defiant disorder. This text outlines the impact of biological factors on children, examining the influences of toxins and dietary deficiencies.